NITROGEN IN THE INITIAL GROWTH AND PHOTOSYNTHESIS PHOTOCHEMICAL IN Alibertia sessilis (Vell.) K. Schum - Santos, Cleberton Correia; Ortega, Rafael da Cruz Chiquito; Silvério, Juliana Milene; Poyer, Henrique Chacha; Scalon, Silvana de Paula Quintão; Vieira, Maria do Carmo (Floresta, 2020)
The use of N fertilizers can contribute to seedling production in native species, such as Alibertia sessilis (Vell.) K. Schum, a fruit plant of the Cerrado ecoregion. Considering that there are few studies on mineral nutrition for this species, the aim of this study was to evaluate the effect of N on the growth and photosynthesis photochemical of A. sessilis. The experiment was carried out in plastic pots in a greenhouse with five N (urea) concentrations: 0, 25, 50, 75, and 100 mg kg-1. The experimental design used was a randomized block design with four repetitions. At day 180 after transplantation, morphometric and photochemical characteristics, including biomass and seedling quality, were evaluated. Seedling survival, the stem diameter of the harvest, and the height/diameter ratio were not influenced by N. The maximum height was 14.38 cm with 54.2 kg-1 N. The greatest number of leaves and value of the chlorophyll index were found in seedlings produced with maximum doses of N. The photochemical characteristics of photosynthesis, except initial fluorescence, were positively influenced with N concentrations between 60-85 mg kg-1 N. The largest fresh leaf and stem biomass was 2.391 and 0.257 g plant-1 with 54.0 and 33.0 mg kg-1 of N, respectively. The multivariate analysis of the major components explained 79.81% of the remaining data variability. The seedlings of A. sessilis responded positively during the initial growth phase, reflected in their biomass, with N concentrations close to 50.0 mg kg-1.